Competencias investigativas y su relación con la producción científica en el profesorado de la Facultad de la Salud Humana. - González Guambaña, Katherine Michelle (2024)
The university professor is a professional who assumes different roles in higher education institutions and is obliged to demonstrate the results of his performance as a trainer and researcher. It is recognized that whether a professor has published or not does not guarantee that they have or develop greater research competencies than others, however, it corresponds to one of the indicators for the accreditation of university careers. In view of this, the objectives of this research were to recognize the research competencies possessed by professors, to identify the main indicators of scientific production and to find the relationship between these two variables. It was a quantitative, descriptive and cross-sectional study, the method used was the survey, for which a questionnaire was applied to 64 teachers of the five careers of the Faculty of Human Health, the instrument is validated by the judgment of experts and has a high reliability that allowed obtaining the following results: despite the teachers' mastery of concepts on the importance of science (78.13%) and research (71.87%) as generators of knowledge and the use of updated bibliographic sources (43.75%), they only sometimes use it to solve problems in their daily academic life (31.25%), because they encounter difficulties in the required procedures and guidelines (45.31%), especially when preparing papers (45.31%) and when writing the summary in a language other than their mother tongue (48.44%). There is a significant percentage of teachers (21.9%) who have not published in the last five years, and those who have published between 1 and 5 (80%) articles. In addition, it was found that those who have less scientific production develop lower research competencies. Key words: research professor; scientific production; teacher competencies; academic articles; research competencias.